Scientific Publications of Jadavpur University, West Bengal: Scientometric Analysis (LIS TODAY, 2024)
[The present study analyses the scientific productivity of Jadavpur University for the study period from 2002 to  2021 using the SCOPUS database. The retrieved data has been analyzed on the following parameters;  document-wise distribution of the publication, authorship pattern, Collaborative indices, most preferred  journals, times series analysis, and Bradford's law test. Journal articles are the most preferred form of  publication type of documents by the Jadavpur University. The highest growth rate of the Jadavpur University  was found 0.28 with 450 publications during the year 2003. It is observed from the study that the relative  growth rate has increased and the doubling time has decreased during the study. Time series analysis  calculation proved that there is a positive growth in the research output of Jadavpur University publications.]
Keywords: Scientometrics; Exponential Growth Rate; Co-Author Index; Bradford Law; Time series analysis